Decommissioning vs. repowering of offshore wind farms—a techno-economic assessment - Jadali, A. M.; Ioannou, A.; Salonitis, Konstantinos; Kolios, Athanasios (Springer, 2021)
Offshore wind turbines are normally designed for a nominal service life of 20 to 25 years; however, with a significant number of units approaching the second half of their service life, the discussion on selecting the most appropriate end-of-life scenario becomes ever more relevant. Scenarios to be investigated mainly include decommissioning, repowering, or service life extension, while such decisions depend on a number of criteria which should be taken into account and should ultimately inform a techno-economic and risk assessment. This paper performs an initial comparative assessment between two of these scenarios, repowering and decommissioning, through a purpose developed techno-economic analysis model which calculates relevant key performance indicators. The economic model of risk aversion is further adopted to calculate the certainty equivalent of LCoE (levelized cost of energy) based on each of the examined end-of-life scenarios and a stochastic expansion of the deterministic model. An application to a typical, hypothetical offshore wind farm qualifies the full repowering scenario as the prevailing option, under the assumptions considered, with a lower amount of risk premium (1.136 £/MWh) and certainty equivalent (69.821 £/MWh) in comparison to other scenarios, reducing LCoE by nearly 35% compared to partial decommissioning and 36.5% compared to full decommissioning.
Keywords: Certainty equivalent; Risk premium; Levelized cost of energy; Decommissioning; Repowering; End-of-life scenarios